Removing the Causes of War, Mitigating its Horrors, and Settling International Disputes Peacefully - Keith, Kenneth J (Victoria University of Wellington Law Review, 1999)
This article focuses on The Hon Sir John Salmond’s three lectures whose topics are listed in the title. Sir Kenneth Keith argues that Salmond’s discussions on international diplomacy raise recurring questions of legal philosophy and method, and about the roles of the university lawyer. The author notes that Salmond’s lectures ultimately show a healthy interaction between the various professional and public roles of lawyers.